Corporate Governance Structures and Financial Constraints in Multinational Enterprises – An Analysis in Selected European Transition Economies on the Basis of the IWH FDI Micro Database 2013 – - Andrea Gauselmann; Felix Noth (Leibniz-Institut für Wirtschaftsforschung Halle (IWH), 2015)
In our analysis, we consider the distribution of decision power over financing and investment between MNEs' headquarters and foreign subsidiaries and its influence on the foreign affiliates' financial restrictions. Our research results show that headquarters of multinational enterprises have not (yet) moved much decision power to their foreign subsidiaries at all. We use data from the IWH FDI Micro Database which contains information on corporate governance structures and financial restrictions of 609 enterprises with a foreign investor in Hungary, Poland, the Czech Republic, Slovakia, Romania and East Germany. We match data from Bureau van Dijk's AMADEUS database on financial characteristics. We find that a high concentration of decision power within the MNE's headquarter implicates high financial restrictions within the subsidiary. Square term results show, however, that the effect of financial constraints within the subsidiary decreases and finally turns insignificant when decision power moves from headquarter to subsidiary. Thus, economic policy should encourage foreign investors in the case of foreign acquisition of local enterprises to leave decision power within the enterprise and in the case of Greenfield investment to provide the newly established subsidiaries with as much power over corporate governance structures as possible.
urn:nbn:de:gbv:3:2-36890
Keywords: F23; G11; G34; R11; 330; corporate governance; financial restrictions; multinational firms; European post-transition economies